Assessment of Spoilage Microbiota of Rainbow Trout (Oncorhynchus mykiss) during Storage by 16S rDNA Sequencing - Guangqing Du; Yuanming Gai; Hui Zhou; Shaoping Fu; Dawei Zhang (Journal of Food Quality)
Due to the high contents of protein and fat in rainbow trout, it is highly susceptible to spoilage, which limits the storage and transportation processes. Exploring the spoilage microbial community during rainbow trout storage is essential to develop an effective preservation method. Here, the changes in the total bacterial colony and total volatile base nitrogen (TVB-N) during the storage of rainbow trout were investigated. Storage at 0 °C can effectively slow down the spoilage process with bacterial counts and TVB-N contents decreased from 8.7 log CFU/g and 18.7 mg/100 g obtained at 4 °C to 5.6 log CFU/g and 14.5 mg/100 g, respectively. 16S rDNA high-throughput sequencing results showed that the diversity of microbial genera decreased during storage. Acinetobacter, Pseudomonas, and Shewanells gradually became the dominant spoilage genera with contents of 59.9%, 18.6%, and 1.7%, respectively, in the late stage of storage. The spoilage abilities of bacteria belonging to the Pseudomonas and Shewanells genera were analyzed. Shewanella sp. S5-52 showed the highest level of TVB-N content (100.6 mg/100 g) in sterile fish juice, indicating that it had a strong spoilage ability. This study confirmed the dominant spoilage bacterial genera and evaluated the spoilage abilities of isolated strains during the storage of rainbow trout, which laid the foundation for further investigation of the spoilage mechanism of rainbow trout and other aquatic products.